Criterion Validity of a Computer Adaptive Universal Screener to an End-of-Year State Mathematics Assessment. Issue 4 (8th August 2022) - Peltier, Corey; Vannest, Kimberly J.; Tomaszewski, Brianne R.; Morin, Kristi; Sallese, Mary Rose; Pulos, Joshua M.
ABSTRACT: The current study examined the criterion validity of a computer adaptive universal screener with an end-of-year state mathematics assessment using extant data provided by a local education agency. Participants included 1, 195 third through eighth graders. Correlational analyses were used to report predictive and concurrent validity coefficients for the universal screener with the end-of-year state mathematics assessment. Moderation analyses were performed to examine the extent to which criterion validity estimates were differential for certain demographic variables. Criterion validity coefficients were above the 0.70 threshold suggested for universal screeners for 5 of 6 grades. The criterion validity of the universal screener to the state assessment was differential for many demographic groups: gender, special education status, free or reduced meals status, and section 504 status. Implications for future research and practice are discussed.